Intermittent hypoxia-hyperoxia therapy in patients with chronic disorders of consciousness after severe acquired brain injury: interim study results - A. A. Ilina; M. M. Kanarskii; M. V. Petrova; D. V. Ilin; V. E. Zakharchenko (Messenger of ANESTHESIOLOGY AND RESUSCITATION, 2026)
Introduction . Chronic disorders of consciousness (DoC) after severe brain injury are observed in patients requiring prolonged intensive care treatment and rehabilitation. Given the high medication burden, safe non-pharmacological approaches to consciousness recovery remain clinically relevant. One such approach is intermittent hypoxia–hyperoxia therapy (IHHT). The objective was to assess the effect of IHHT on the dynamics of consciousness recovery in patients with DoC after severe acquired brain injury. Materials and methods . Interim results of a prospective study are presented. Patients with DoC were assigned to a control group (n = 25), receiving standard therapy, and a main group (n = 24), in which treatment was supplemented with a 15-day IHHT course. The primary endpoint was an increase in the total Coma Recovery Scale–Revised (CRS-R) score by ≥3 points by day 30. Changes in the total CRS-R score and subscales, as well as transitions between diagnostic levels of consciousness, were additionally analyzed. Results . By day 30, a ≥3-point CRS-R increase was registered in 15/24 patients in the main group (62.5%) and 6/25 patients in the control group (24.0%); p = 0.009. The total CRS-R score by day 30 was higher in the main group: 16 [8.25; 22] versus 9 [6; 14] points; p = 0.022. CRS-R subscale analysis revealed significant between-group differences in auditory and visual functions, communication, and arousal. Improvement in the diagnostic level of consciousness was more frequent in the main group: 17/24 versus 7/25 patients; p = 0.004.Conclusion. In patients with DoC, adding IHHT to complex therapy was associated with more pronounced CRS-R improvement and a higher diagnostic level of consciousness by day 30.